Effects of Water Stress on the Physiological and Biochemical Responses of Mangosteen (Garcinia Mangostana L.) Plant - Adwirman (2006)
Water is one of the environmental factors that influence plant growth and production. Water is also one of the main components in photolysis during light reaction photosynthesis pathways. Lack of water, therefore, 'severely decreases plant growth and production. Several experiments have been conducted to study the effects of water deficit on m. .a ngosteen vegetative growth and toward yield production. Experiments were . . conducted in the green house unit of Faculty of Agriculture, Universiti Putra Malaysia, Serdang, and in Malaysian Agricultural Research and Development Institute (MARDI), station in Kedah Darulaman on young plants (two years old seedlings) and productive plants, respectively. Other experiments with hydrogel (water absorbance and slow release) and partial root .drying (PRD) treatments to . . increase plant water use efficiency were also conducted. These experiments were conducted at the green house unit of Faculty of Agriculture, Universiti Putra ~ a l a ~ s iSae,r'd ang. Overall results from these experiments showed that mangosteen plants physiological and biochemical have good response toward water stress or water deficit. Water stress or.' deficit produced significant decrease in plant leaf water potential, stornatal conductance and photosynthesis rate. Measurements on abscisic acid, peroxidase and proline concentrations were also taken. Water deficits were found to increase mangosteens leaf abscisic acid. However, water stress did not significantly affect . . . . plants peroxidase and proline concentration. Water stress also decreased plant leaf increment. While hydrogel treatment with dose 0.1-0.5 % did not produce positive result, the lower dose (0.02-0.10%) showed good finding, which in these treatment, plant physiological appearance remain normal. It was suggested that hydrogel with dose 0.06 % could to be applied to mangosteen plant to assist the plant conserve soil water availability and increase'water used efficiency. The partial rootzone drying (PRD) treatment showed very interesting findings. PRD . treatment was found to reduce water use by 50% compared to normal watering. Reducing. water use by 50% in PRD treatment also did not decrease leaf water potential, stomata1 conductance and net photosynthesis. In other words, PRD treatment was able, to maintain plants in the normal condition. PRD treatment also s. i.g nificantly produced higher proline concentration than that on water stressed . . treatment. It is concluded that PRD treatment could be used as water saving for mgngosteen in vegetative stage. Field experiments during the productive stage of mangosteen conducted for two years indicated interesting results. Water stress or deficit increased mangosteen leaves and flag leaves (leaves below flower) total nonstructural carbohydrate (TNC). However, increasing in TNC was not followed by a subsequent increase in fruit yield due to lower fruit set and higher h i t drop percentage. Generally, water stress or water deficit reduced maxigosteen fruit yield. Increasing water supply from 50 Lltreelday to 200 Lltreelday in .the field water stress significantly enhanced total harvested fruit . weight. In the first year of the field experiment, there was no difference in soil moisture. In this condition, raising the amount of irrigation water led to higher average fruit weight. However, in the second year of the field experiment which was drier than the first year, raising the amount of irrigation water did not seem to increase fruit size and average fruit weight. Nevertheless, fruit drop percentage was not affected by the increase amount of irrigation water in the first year, but decreased in the second year of experiment.